2017
DOI: 10.7717/peerj.3537
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation and psychological factors: a systematic review

Abstract: BackgroundPsychological factors have been suggested to have an influence in Atrial Fibrillation (AF) onset, progression, severity and outcomes, but their role is unclear and mainly focused on anxiety and depression.MethodsA systematic electronic search had been conducted to identify studies exploring different psychological factors in AF. The search retrieved 832 articles that were reviewed according to inclusion criteria: observational study with a control/comparison group; use of standardized and validated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 58 publications
1
19
0
1
Order By: Relevance
“…Atrial fibrillation (AF) is the most common heart arrhythmia in clinical practice which is expected to increase dramatically within next decades due to the prolongation of life expectancy and the improvements in diagnosis [ 1 ]. According to estimates, AF currently affects over 6 million patients in Europe and approximately 2.3 million in the United States [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is the most common heart arrhythmia in clinical practice which is expected to increase dramatically within next decades due to the prolongation of life expectancy and the improvements in diagnosis [ 1 ]. According to estimates, AF currently affects over 6 million patients in Europe and approximately 2.3 million in the United States [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Depression and anxiety have been associated not only with TTS (Nayeri et al, 2018), but also with elevated risk of developing other cardiac diseases (Janszky et al, 2007;Kendler et al, 2009;Gustad et al, 2014;Galli et al, 2017). A recent retrospective cohort study (Nayeri et al, 2018) found that preexisting psychopathologic disorders (anxiety, mood disorders, and schizophrenia) were associated with an increased risk of recurrent TTS, but not to survival.…”
Section: Discussionmentioning
confidence: 99%
“…Atrial fibrillation (AF) is a common disorder of cardiac rhythm (estimated prevalence in people older than 15 years in Italy is 2% ( Zoni-Berisso et al, 2013 ) that increases with age. Psycho-emotional factors seem to be associated to AF in different ways ( Galli et al, 2017 ). AF predisposes to arterial thrombosis and systemic embolism, the reason why patients need long-term antithrombotic prophylaxis with oral anticoagulants (OACs), as vitamin K antagonists (VKAs).…”
Section: Introductionmentioning
confidence: 99%